Acústica como interseccionalidade entre a Física e a Música: proposta de sequência de ensino de Física Acústica a partir de elementos musicais à luz dos "três momentos pedagógicos" - Paula, Wenderson Venceslau Barroso de (2025)
As such a widespread and engaging form of artistic expression, music has the potential to stimulate emotions, memories, reflections and create connections. In the context of teaching Physics at the secondary level, music and its elements can act as an effective teaching tool in the teaching and learning processes, capable of providing students with a dynamic and enjoyable learning experience, and can therefore facilitate the understanding of complex scientific concepts, which are commonly treated as too abstract or intangible by students. In this paper, we present a proposal for a didactic sequence for teaching basic concepts of Acoustic Physics to second-year high school classes, using the "Three Pedagogical Moments" (3MP) as theoretical and methodological support. In this sequence, music is not used as a mere filler for motivational space, but is, above all, considered as an interface that, like Physics, has Acoustics as an intersectional field. In this work, we outline a sequence of teaching Acoustic Physics that includes nine classes in total, the main objective of which is to make students understand, through a didactic sequence developed from a series of generating problematizations and applications, the concepts related to Acoustic Physics through music, using, as didactic examples, some related devices, such as microphones, tuning forks, guitars and sound tubes (built with PVC pipes). We verified, during our research, that the proposed objectives were all achieved with the adopted methodology and that the students felt involved and motivated throughout the process.